RELATIONSHIP OF LIFE STYLE CHOICES ON BODY FAT MASS IN YOUNG ADULTS - Rehman, Rehana; Shaikh, Saif ullah; Syed, Sadiqa; Shakeel, Nayyab (Journal of Ayub Medical College Abbottabad, 2010)
Background: Healthy diets and regular, adequate physical activity are major factors in the promotion and maintenance of good health throughout entire life course. Accumulation of fat occurs whenever energy consumed by food and drinks exceeds that which can be utilised by an individual’s metabolism and physical activity. The objective of this study was to estimate the effect of lifestyle characteristics of a representative segment of medical students in terms of fast food preferences and participation in physical activity with respect to Body Mass Index (BMI). Methods: This cross-sectional study was carried out in Physiology Department, Bahria University Medical & Dental College, Karachi on 192 students of 1st and 2nd year MBBS. Body Mass index of students was calculated. They were classified into 4 groups with BMI ‰¤18.5, 18.6-23, 23.1-25 and ‰¥25 respectively. A life style questionnaire, based on preferences for healthy/unhealthy food, dietary habits and participation in physical activity was filled. Results: Most of medical students (65%) had BMI less than 23. It was because of selection of healthy dietary pattern with nutritious food (p<0.09) and participation in outdoor games (p<0.03). Males who had high BMI showed a tendency to daily intake of fast food (p<0.03). Walking in both the sexes had a positive impact in maintaining normal BMI (p= Males<0.04, females<0.001). Conclusion: Obesity can be prevented by innovative approaches, easiest of which is to promote active life styles with intake of healthy diet and involvement in physical activity. Keywords: BMI, obese, overweight